Drug-related police encounters across the globe: How do they compare? - Hughes, C.; Barratt, Monica; Ferris, J.; Maier, L.; Winstock, A. (Elsevier BV, 2018)
© 2018 Elsevier B.V. Background: Drug law enforcement subsumes the majority of drug policy expenditure across the globe. Fuelled by knowledge that much of this investment is ineffective or counter-productive there have been increasing calls for cross-national comparisons to identify where policing approaches differ and what types of approaches may be more effective. Yet, to date cross-national comparison of drug law enforcement has proven a methodologically hazardous affair. Using a new drug policing module added to the 2017 Global Drug Survey, this study seeks to provide the first cross-national comparison of the incidence, nature and intensity of illicit drug-related police encounters amongst people who use drugs. Methods: The Global Drug Survey was administered in late 2016. Across 26 countries including Australia, Germany, Italy, Mexico, Switzerland, the UK and the USA a total of 45,942 people who had recently used drugs completed the drug policing module. Key variables assessed included the incidence and frequency of drug-related police encounters in the last 12 months that involved: a) being stopped and searched; b) encountering a drug detection dog; c) being given a caution or warning; d) being charged and arrested; and e) paying a bribe. Multi-level models were used to control for pre-existing national differences in drug use prevalence and non-drug specific policing (including the total number of police personnel in each country). Results: Drug-related police encounters were most commonly reported in Italy and Scotland. Conversely, police encounters were most likely to lead to arrest in Norway, Finland and Sweden. The type and locations of encounters further differed across countries, with for example stop and search most reported in Greece and Colombia, and encounters with drug detection dogs most reported in Scotland, Italy, UK and Australia. Multi-level models showed that the incidence of reported policing encounters continued to differ significantly across countries after controlling for pre-existing national differences in drug use prevalence and policing, and that drug policing encounters were 4 to 14 times more common in some nations than others. Conclusion: The findings unearth significant cross-national differences in the incidence and nature of drug-related policing of people who use drugs. This suggests that there may be opportunities for countries to learn from each other about how and why they differ, and the potential benefits of switching to lower intensity modes of drug policing.